Psychological Disturbance among Dentistry Students during COVID-19 Restriction - Agus Ardinansyah; Nur Hidayati Nosi; Ridhayani Hatta; Dhihram Tenrisau; Nilna Saádatar Rohmah; Muhammad Zakki Saefurrohim (Lembaga Penelitian Universitas YARSI, 2026)
Study environment became the factors triggering the anxiety, stress, and depression among students. During the COVID-19 restriction (2020-2022), the teaching and learning activities were shifted from campus to online class affecting the student’s mental state. The objectives of this study are to explore the factors that possibly contributed to anxiety, stress, and depression to pre-clinical and clinical students of YARSI Dentistry Faculty. The research was a cross-sectional study with the Stratified Random Sampling with the total of 425 both pre-clinical and clinical students of YARSI Dentistry Faculty. The total of 266 students (188 pre-clinical and 76 clinical) became the sample in this study with DASS (Depression, Anxiety, Stress Scale) questionnaire with Google Form. We utilized the Logistic Regression Binomial for statistical analysis to estimate OR and find the predictors. The marriage status, housing, and length of study were considerably major predictor for anxiety, stress, and depression among students in DASS measurements. In multivariate analysis, renting accommodation was a considerable contributor for anxiety (AOR = 5.34 (3.1-9.41)) than living with family. Similarly, renting accommodation also affected both stress (AOR = 5.34 (3.1-9.41)) and depression (AOR = 6.57 (3.19-9.41)). In addition, length of study was possible a predictor (AOR = 1.79 (1.04-3.1)). The Study environment and social condition were possible contributing to mental state of students during COVID-19 restriction. The psychological assistances are considered important for students during COVID-19 restriction, especially the students with renting accommodation and studying more than 3 years.